ALTITUDE The National Charter for Universal Design in Tertiary Education: Technical Report - Banks, Joanne (AHEAD Educational Press, 2024)
Ireland’s education system is at a critical stage in its development towards inclusion. Greater diversity in the student population, national and international policy emphases on the right to an inclusive education for every learner, and the evolution of technology in education in recent decades, have drawn attention to the need for a more inclusive model of education across all sectors. Within tertiary education, there is a growing momentum towards an inclusive, universally designed, and unified sector in both policy and practice. In Ireland, further and higher education has, over recent decades, had to reflect on traditional policies, structures, systems of support, and pedagogical approaches for students. It is from this period of reflection that calls for a National Charter in Universal Design in Tertiary Education, or ALTITUDE, have arisen. Research shows that Ireland has a robust national policy commitment to a universal design (UD) approach, and evidence of engagement of individuals in professional development and local implementation is plentiful. Despite these developments, however, evidence also shows that a commitment to UD is not evident in the institutional strategies and policies of many higher education institutions and education and training boards (Healy et al., 2023). The ALTITUDE Charter seeks to support institutions to address this gap and embed UD more sustainably over time in their structures and practices. This Technical Report acts as an accompanying document to ALTITUDE, the National Charter for Universal Design in Tertiary Education, launched in the Spring of 2024. The Charter is one of three related components made up of the Charter itself, this Technical Report, and an Implementation Toolkit. The Technical Report is divided into four sections: 1. It provides a contextual overview for the Charter, outlining the rationale for its development and the challenges and enablers to an inclusive tertiary education system in Ireland and internationally. 2. It gives an overview of the origin and development of the Charter before highlighting the structure of the Charter, its strategic foundation and four pillars, aimed at increasing accessibility, flexibility and usability in tertiary education. The four pillars include: Teaching and Learning; Supports Services and Social Engagement; Physical Environment and Digital Environment. 3. It examines how the Charter aligns with existing international policies and national policies with a specific focus on Charter alignment with existing tertiary education policies and funding mechanisms. 4. The Technical Report concludes with a focus on Charter implementation and examines how this Charter can support institutions wishing to create more inclusive environments for students and staff. It provides an overview of how institutions can begin to implement the Charter with the formation of an Implementation Committee/Working Group and use of the associated Toolkit. This section concludes with an overview of the significance of the role of policy makers and national bodies in supporting institutions to adopt and implement the Charter. The cross-sectoral development of the ALTITUDE Charter and its associated outputs represents a landmark moment for the tertiary education sector, signalling its intent to place human diversity at the heart of its design and delivery. It commits to a system where all learners are transformatively included through a universal design approach, which fosters student success for all. Underpinning this, is an effort to further operationalise a culture of shared responsibility for universal design, access & inclusion, by supporting the development of organisational structures which foster an ‘everyone’s business’ approach to inclusion. By adopting the Charter, tertiary education providers are invited to build on existing innovative policies and practices across the sector, using the Charter as a vehicle for greater coherence and collaboration on access and inclusion, both within and across institutions.
PUBLISHED
Keywords: Inclusive Society; Adult & Continuing Education; Education policy; Higher Education; Inclusive Education; Education